2016
DOI: 10.18089/tms.2016.12115
|View full text |Cite
|
Sign up to set email alerts
|

The role of satisfaction in cultural activities’ word-of-mouth. A case study in the Picasso Museum of Málaga (Spain)

Abstract: Keywords: Cultural tourism, word-of-mouth, museums. ResumenEl boca a boca se ha convertido en un área relevante de la investigación en la actividad turística en las últimas décadas. Sin embargo, los efectos en esta recomendación de las emociones de los turistas es un área poco desarrollada, sobre todo en el turismo cultural. Este turismo es el segundo sector más importante en términos de número de llegadas de turistas en los países con turismo significativo, como España. Haciendo un balance de los avances reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…WOM has been extensively studied in the tourism sector, and it has been shown that communication on tourist destinations has to take into account the emotions that customers experience during their visits to the destination [24].…”
Section: Electronic Word Of Mouth (Ewom)mentioning
confidence: 99%
“…WOM has been extensively studied in the tourism sector, and it has been shown that communication on tourist destinations has to take into account the emotions that customers experience during their visits to the destination [24].…”
Section: Electronic Word Of Mouth (Ewom)mentioning
confidence: 99%
“…Padilla-Meléndez and Santos found that eliciting positive emotions, such as excitement and enthusiasm, increased levels of satisfaction and potential for positive word-of-mouth communication in a sample of college students visiting a museum exhibit in Spain. 4 In contrast, Nawijn and Fricke found that experiencing negative emotions predicted higher revisit intentions and increased potential positive word-of-mouth communication than experiencing positive emotions in a sample of museum visitors in Germany. 5 Commercially, emotions can have a strong impact on the behavior of consumers.…”
mentioning
confidence: 92%